Company Growth, Company Size, and Investment Decisions on Banking Company Value: Pertumbuhan Perusahaan, Ukuran Perusahaan, dan Keputusan Investasi Terhadap Nilai Perusahaan Perbankan - Amelia, Lailatul; Prapanca, Detak (Indonesian Journal of Innovation Studies, 2023)
This study aims to examine the effect of firm growth, firm size, and investment decisions on firm value. The approach used in this research is a quantitative approach. The population in this study is banking companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling method. The sample in this study was 72 companies listed on the Indonesia Stock Exchange in 2018-2020. The data used in this study is secondary data taken from the Indonesia Stock Exchange. Analysis of the data used in this study is Eviews version 10 with the aim of testing Company Growth (X1), Company Size (X2), and Investment Decisions (X3) Against Firm Value (Y). The results of this study indicate that simultaneously there is a significant influence between company growth, company size, and investment decisions on firm value. While partially, the variables of firm growth and firm size have no significant effect on firm value, while the investment decision variable has a significant positive effect on firm value.